Globalization and environment : discourse, policies and Practics - Verma, Manish K. (ed.) (Jaipur, 2015)
The inordinate process of globalization has seen an intense movement of the world - on social, cultural, economic, political, and ecological fronts - leading to the integration, unification, homogenization, and transformation of society and environment at the global level. Scholars have varied perceptions about the nature, magnitude, discourse, policies, and practices associated with globalization. It is an important issue of concern, whether to consider globalization benign and a blessing or a curse for mankind. Nevertheless, the way globalization process has operated during the last couple of decades, it has become clear that it is an evolving reality. This volume comprehensively examines the inter-linkages between globalization, the environment, and society by taking into consideration the strands of emerging discourse - the ecological dimension, the social dimension, and the economic dimension. Each strand of thought helps to shed light on one major area of debate, evolved at the global level due to advent of globalization. [Subject: Sociology, Environmental Studies, Development Studies, Globalization, Politics]
Keywords: Globalization-Economic aspects